Sinterability and microstructure evolution during sintering of ferrous powder mixtures - Demétrio,Kétner Bendo (2013)
The present work is focused on ferrous powder metallurgy and presents some results of a development of a suitable masteralloy for use as an additive to iron powder for the production of sintered steels. The masteralloy was produced by melting a powder mixture containing approximately Fe + 20% Ni + 20% Mn + 20% Si + 1% C (wt%), in order to obtain a cast billet that was converted into fine powder by crushing and milling. It was observed presence of SiC in the masteralloy after melting that is undesirable in the alloy. Si element should be introduced by using ferrosilicon. Sintered alloys with distinct contents of alloying elements were prepared by mixing the masteralloy powder to plain iron powder. Samples were produced by die compaction of the powder mixtures and sintering at 1200 °C in a differential dilatometer in order to record their linear dimensional behaviour during heating up and isothermal sintering, aiming at studying the sinterability of the compacts. Microstructure development during sintering was studied by SEM, XRD and microprobe analyses.